High-temperature oxidation and hot corrosion behavior of the Inconel 738LC coating with and without Al2O3-CNTs - Alsultani Kadhim F.; Majidi Hassan Sh.; Abdulameer Sara; Karkush Mahdi (Journal of the Mechanical Behavior of Materials, 2023)
The high-temperature corrosion of turbine blades poses a serious threat to the efficiency of electrical gas power stations, which results in heavy economic losses. In the present study, the Inconel 738 low-carbon steel utilized in the turbine blades was coated on alumina (Al2O3) in a variety of percentages of carbon nanotubes (4, 6, and 8 wt%) using the plasma spray technique. The behavior of the Inconel 738LC alloy with and without artificial ash (67 wt% H2SO4 and 33 wt% V2O5) at different temperatures (650, 750, 850, and 950°C) was investigated. The cycles of hot corrosion and oxidation were achieved in an electric furnace for 10 cycles of 5 h each. After each cycle, the weight changes were measured and recorded. The SEM and XRD achieved for all the specimens were noted, before and post the corrosion.